Cyfra21.1 - Specific maker for dingnosis of lung cancer - Chac, Le Dinh; Luong, Nguyen Tai; Huan, Le Quang (Academia Journal of Biology, 2012)
Today, there are many modern methods used to diagnose cancer. However, the use of indicator of antigens to diagnose cancer is one of the new method and has high reliability. In fact, several antigens have been used for the diagnosis of lung cancer, such as, Carcinoembryonic antigen (CEA), 19cyfra21.1 cytokeratin, neuron specific enolase (NES), and CA125. that showed high efficacy but still face to many restrictions as the sensitivity of these antigens is not specific to non-small cell lung carcinoma. The use of Cyfra21.1 antigen is one of the new methods of diagnosis and orientation of lung cancer treatment in Vietnam that overcomes the limitations mentioned abobe and has high efficiency. Cyfra21.1 structure is a fragment of cytokeratin 19 (one of an intermediate fiber structure of the cell frame) and deternine antigen of Cyfra 21.1 in the range from 311 to 368 amino acids of molecular cytokeratin 19. This is a highly specific indicator for lung cancer, that is indicated by the specific sensitivity to majority of lung cancer (NSCLC: SCLC = 8.6: 2.5 ng/ml, p = 0.006). Therefore, Cyfra 21.1 is considered as a worthy indicator which is useful in the diagnosis and orientation treatment of non-small cell lung carcinoma.